2007
DOI: 10.1523/jneurosci.4141-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Neurosteroid Sensitivity of Synaptic Inhibition and Altered Location of the α4 Subunit of GABAAReceptors in an Animal Model of Epilepsy

Abstract: In animal models of temporal lobe epilepsy (TLE), neurosteroid sensitivity of GABA A receptors on dentate granule cells (DGCs) is diminished; the molecular mechanism underlying this phenomenon remains unclear. The current study investigated a mechanism for loss of neurosteroid sensitivity of synaptic GABA A receptors in TLE. Synaptic currents recorded from DGCs of epileptic animals (epileptic DGCs) were less frequent, larger in amplitude, and less sensitive to allopregnanolone modulation than those recorded fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 51 publications
6
80
0
1
Order By: Relevance
“…It was shown that GABA A -receptor-mediated inhibition was reduced in the epileptic rats (Isokawa 1996;Kobayashi and Buckmaster 2003). Several other studies, interestingly, demonstrated that mIPSC amplitude was enhanced in these animals (Cohen et al 2003;Gavrilovici et al 2006;Leroy et al 2004;Nusser et al 1998;Sun et al 2007). In contrast to the possible mechanisms for the acute changes we observed, alterations of GABAergic phasic inhibition during epilepsy are likely related to long-term changes in GABA A -receptor expression and/or function such as regulation of receptor gene expression and degradation or synthesis of multiple receptor subunit proteins.…”
Section: Plastic Changes Of Gaba a -Receptor Function During Developmmentioning
confidence: 74%
“…It was shown that GABA A -receptor-mediated inhibition was reduced in the epileptic rats (Isokawa 1996;Kobayashi and Buckmaster 2003). Several other studies, interestingly, demonstrated that mIPSC amplitude was enhanced in these animals (Cohen et al 2003;Gavrilovici et al 2006;Leroy et al 2004;Nusser et al 1998;Sun et al 2007). In contrast to the possible mechanisms for the acute changes we observed, alterations of GABAergic phasic inhibition during epilepsy are likely related to long-term changes in GABA A -receptor expression and/or function such as regulation of receptor gene expression and degradation or synthesis of multiple receptor subunit proteins.…”
Section: Plastic Changes Of Gaba a -Receptor Function During Developmmentioning
confidence: 74%
“…There is evidence showing that epilepsy models result in reduced expression of the ␦ subunit in the dentate gyrus (Zhang et al, 2007), although in a mouse model of temporal lobe epilepsy, ␣4 and ␥2 were increased (Peng et al, 2004). A marked decrease in neurosteroid sensitivity was observed in epileptic rats (Mtchedlishvili et al, 2001;Sun et al, 2007). High levels of ␦ expression, in contrast, would be expected to attenuate the seizure state.…”
Section: Discussionmentioning
confidence: 98%
“…Research indicates that in high concentrations tramadol exerts an inhibitory effect on gammaaminobutyric acid (GABA) receptors [12,13]. Inhibition of GABA receptors has been found to potentiate the severity of seizures in animal models [13,14]. In addition, GABA receptor inhibition induced by tramadol can be secondary to its opioid receptor agonist activity [13], and continuing this agonist activity on opioid receptor has been proven to precipitate seizure due to inhibition of GABA pathways [15,16].…”
Section: Introductionmentioning
confidence: 99%